2015
DOI: 10.3390/ijms160921931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of Chitin Nanofiber on Plasma Metabolites and Gut Microorganisms

Abstract: The aim of this study was to examine the effects of oral administration of chitin nanofibers (CNFs) and surface-deacetylated (SDA) CNFs on plasma metabolites using metabolome analysis. Furthermore, we determined the changes in gut microbiota and fecal organic acid concentrations following oral administrations of CNFs and SDACNFs. Healthy female mice (six-week-old) were fed a normal diet and administered tap water with 0.1% (v/v) CNFs or SDACNFs for 28 days. Oral administration of CNFs increased plasma levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…In a previous study, we isolated chitin nanofibers from crab shells and prepared them using a simple mechanical treatment [2]. Chitin nanofibers have a characteristic morphology [3], high surface-to-volume ratio [4], high mechanical strength [5,6], and efficient biological properties [7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we isolated chitin nanofibers from crab shells and prepared them using a simple mechanical treatment [2]. Chitin nanofibers have a characteristic morphology [3], high surface-to-volume ratio [4], high mechanical strength [5,6], and efficient biological properties [7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…30,31) In addition, it has been reported that the oral administration of chitin nanofibers activated the functions of gut microorganisms and increased the plasma level of ATP. 32) These functionalities are thus expected to be higher in Gf433, which contains more chitin.…”
Section: Discussionmentioning
confidence: 99%
“…Such a metabolomics approach can be used to elucidate the mechanism of functional foods. Azuma et al used LC-TOFMS to show that oral administration of chitin nanofiber affects the metabolism of acyl-carnitines and fatty acids, confirming the effectiveness of the technology [33].…”
Section: Introductionmentioning
confidence: 96%
“…A metabolomics approach using capillary electrophoresis mass spectrometry with time-of-flight (CE-TOFMS) makes it possible to quantify charged low-molecular-weight compounds produced by intestinal microbiota with high resolution and high throughput, providing a detailed explanation for the host-intestinal bacterial interactions at the molecular level [32]. Combined with liquid chromatography mass spectrometry with time-of-flight (LC-TOFMS), which is adequate for relatively lipophilic compounds such as fatty acids and bile acids, various biological compounds can be determined and quantified [33]. Such a metabolomics approach can be used to elucidate the mechanism of functional foods.…”
Section: Introductionmentioning
confidence: 99%